Green for us: parental compensation for children’s unsustainable behaviors - Wang, Sili; Zhang, Xiaofei (Frontiers in Psychology, 2025)
This study explores the impact of children’s unsustainable behaviors on parental sustainable actions within family dynamics. Findings reveal that parents exposed to their children’s unsustainable behaviors experience heightened family and environmental responsibility, which motivates them to engage in both private-domain and public-domain sustainable behaviors. These effects are amplified in intergenerational caregiving contexts, where parents compensate for reduced caregiving roles by adopting more sustainable practices. Through four experiments, the research validates the mediating roles of family and environmental responsibility and the moderating influence of caregiver type. This study extends existing theories on intergenerational behavior transmission by highlighting the influence of children’s unsustainable behaviors, offering valuable insights for family education strategies and policy development aimed at fostering sustainability within households.